Developing and implementing programmes for early detection, management and prevention of kidney and cardiovascular disease - Katz, Ivor; Mdleleni, Golebamanag; Shezi, Eugine; Butler, Omar; Gerntholtz, Trevor (SA Heart Journal, 2017)
Chronic Kidney Disease (CKD) and Cardiovascular Disease (CVD) appear to be closely linked but also share common risk factors, making prevention, early detection and management for both diseases similar. In 1998 CVD accounted for 30% of deaths worldwide and in South Africa for almost 40% in the same year. The number of these deaths due to underlying CKD remains unanswered, but it is clear that early detection and management of CKD through screening of patients at high risk, e.g. those with uncontrolled hypertension, diabetes and proteinuria or proteinuria alone, is an appropriate way to control this massive chronic disease burden. Added to this equation is the impact of HIV and/or proteinuria as a cause of CKD and CVD. Against a backdrop of poor control and management of chronic illnesses, there is a growing number of clinicians attempting to tackle this problem through the development of CVD and CKD prevention and early detection programmes. Recognising the common risk factors makes it easier to plan and implement such programmes. This article looks at an “Integrated Model” for managing chronic illnesses, which has been adopted internationally and locally. It discusses the experiences and challenges faced in attempting to implement programmes for CVD and CKD.